A micro-nanostructured gallium oxide, preparation method and application thereof
By using PEG-4000 and DL-aspartic acid as composite soft template agents, GaOOH nanocrystalline microspheres were synthesized and calcined, the problem of poor morphology and size control of nanogallium oxide was solved, and efficient photocatalytic performance was achieved, especially the degradation effect of methyl violet in wastewater treatment was significant.
Patent Information
- Application Number
- CN202210501983.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-05-10
AI Technical Summary
In the prior art, the morphology and size control of nanogallium oxide is not fine enough, which affects its photocatalytic performance, and is rarely used in wastewater treatment.
PEG-4000 and DL-aspartic acid were used as composite soft template agents to synthesize GaOOH nanocrystalline microsphere structures by normal pressure reflux. After calcination, α-Ga2O3 microspheres with good morphology were obtained.
The uniformity of the morphology and size of GaOOH and α-Ga2O3 microspheres was achieved, and their photocatalytic properties were improved, which was specifically manifested as the decolorization rate of methyl violet aqueous solution reached 99.85%.
Smart Images

Figure CN114772630B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of nano metal oxides, and in particular to a micro-nanostructured gallium oxide, a preparation method and application thereof. Background Art
[0002] Nano-metal semiconductor oxides are widely used in sensing, sewage treatment, air purification and other fields. The selection of preparation methods, morphology and size control are still the research hotspots in the fields of nanotechnology and environmental chemistry. Nano-gallium oxide (Ga2O3) is an N-type wide bandgap (4.7-4.9eV) semiconductor oxide with broad application prospects in optoelectronic devices, sensors and catalysis. However, there are relatively few studies on the use of nano-gallium oxide for wastewater treatment. Researchers have been exploring how to control the morphology and size of gallium oxide nanomaterials and thus affect the photocatalytic performance of nano-gallium oxide. At present, the reported preparation methods of nano-gallium oxide include coprecipitation, thermal evaporation, chemical vapor deposition (CVD), thermal annealing, hydrothermal synthesis, microwave method, etc. Low-temperature hydrothermal method is one of the simplest and most effective methods for preparing nanoparticles in liquid phase method. In the reported hydrothermal synthesis methods of nano-gallium oxide, the control of Ga2O3 morphology and size is mainly regulated by temperature, pH value or organic solvents and surfactants. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a micro-nanostructured gallium oxide, a preparation method and application thereof.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A method for preparing micro-nanostructured gallium oxide comprises the following steps:
[0006] S1: Add DL-aspartic acid and deionized water to a reaction bottle, dissolve by ultrasonication, then add PEG solution, gallium nitrate solution and urea to the solution in sequence, stir and mix evenly to obtain a colorless, clear and transparent solution; the mass ratio of DL-aspartic acid to PEG is 0.04:0.4-0.04:6;
[0007] S2: The colorless, clear and transparent solution is then heated from room temperature to boiling until a white precipitate appears in the system and the turbidity no longer increases, and the pH value of the solution is adjusted to 6, and the system is in a sol state;
[0008] S3: Keep the system in a boiling state and continue stirring for 3 hours, then stop heating and cool naturally to room temperature. After natural sedimentation for about 10 hours, separate the precipitate and wash it with distilled water and anhydrous ethanol three times respectively, and finally vacuum dry it at 60°C for 12 hours to obtain the precursor material;
[0009] S4: The precursor material is loaded into a corundum crucible and placed in a muffle furnace, and calcined at 450° C. for 3 h to obtain α-Ga2O3 nanomaterials.
[0010] Furthermore, the molecular weight of PEG is 4000, and the concentration of the prepared PEG solution is 0.1 mol / L.
[0011] Furthermore, the concentration of the gallium nitrate solution is 0.2 mol / L, and the volume mass ratio of the gallium nitrate solution to DL-aspartic acid is 0.5 ml:0.02 g to 0.5 ml:0.05 g.
[0012] The present invention further provides a micro-nano structured gallium oxide obtained by the preparation method as described above.
[0013] The present invention further provides an application of the micro-nanostructured gallium oxide as described above, wherein the gallium oxide can be used for photocatalytic degradation of dye wastewater.
[0014] The beneficial effects of the present invention are as follows: the present invention uses PEG-4000 and DL-aspartic acid as composite soft templates, and synthesizes a GaOOH nanocrystal microsphere structure with relatively uniform morphology and size through a simple atmospheric pressure reflux method, and the particle size is 500nm. After calcination of the microspherical GaOOH nanostructure, α-Ga2O3 microspheres with good morphology retention can be obtained, and the decolorization rate of the methyl violet aqueous solution within 100 minutes is 99.85%, indicating that the experimentally prepared α-Ga2O3 microspheres have good photocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 The XRD spectra of the precursor material and gallium oxide material prepared in Example 1 are shown.
[0017] Figure 2 (b, c) are FE-SEM images of GaOOH nanocrystals and α-Ga2O3, respectively.
[0018] Figure 3 (a, b) are the FT-IR spectra and fluorescence emission spectra of GaOOH nanocrystals and α-Ga2O3, respectively.
[0019] Figure 4FE-SEM images (a, b) and TEM images (c, d) of the precursor material prepared in Comparative Example 1.
[0020] Figure 5 These are the FE-SEM images (a, b) and TEM images (c, d) of the precursor material prepared in Comparative Example 2.
[0021] Figure 6 These are the FE-SEM images (a, b) and TEM images (c, d) of the precursor material prepared in Comparative Example 3.
[0022] Figure 7 The UV-visible spectrum of the photocatalytic degradation of methyl violet by α-Ga2O3 microspheres (a) and the absorbance-time curve of the photocatalytic degradation of methyl violet (b) are shown. DETAILED DESCRIPTION
[0023] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0025] Example 1
[0026] S1: Add 0.0400 g DL-aspartic acid and 4.50 mL deionized water to a 50 mL round-bottom flask, dissolve by ultrasonication, then add 5.00 mL (0.1 mol / L) PEG-4000 solution, 0.50 mL (0.2 mol / L) gallium nitrate solution and 0.3003 g urea to the solution, stir and mix to obtain a colorless, clear and transparent solution;
[0027] S2: A colorless, clear and transparent solution is heated from room temperature to boiling. After 15 minutes, a white precipitate begins to appear in the system. The turbidity of the system increases with the reflux time. When the turbidity stops increasing, the pH value of the solution is about 6, and the system is in a sol state.
[0028] S4: Keep the system in a boiling state and continue stirring for 3 hours, then stop heating and cool naturally to room temperature. After natural sedimentation for about 10 hours, separate the precipitate and wash it with distilled water and anhydrous ethanol three times respectively, and finally vacuum dry it at 60°C for 12 hours to obtain the precursor material;
[0029] S5: The precursor material was loaded into a corundum crucible and placed in a muffle furnace. Gallium oxide powder was obtained after calcination at 450°C for 3 hours for subsequent characterization and analysis.
[0030] The present invention uses DL-aspartic acid and PEG-4000 as composite templates to prepare precursors and gallium oxide. Figure 1 The XRD patterns of the precursor and the sample obtained after calcination are shown in Figure 2. The crystal powder diffraction pattern of the precursor is compared with the XRD standard pattern of GaOOH crystal (JCPDS No.060180), indicating that the precursor prepared by this experimental method is GaOOH nanocrystal. The strongest diffraction peak at 35.72° (2θ) in the pattern corresponds to the (130) crystal plane of GaOOH nanocrystal, and the stronger diffraction peak at 63.74° (2θ) corresponds to the (320) crystal plane of GaOOH crystal. The XRD pattern of the precursor GaOOH nanocrystals calcined at 450°C for 3h is consistent with the PDF standard card (JCPDS No.060503), indicating that the sample obtained after the precursor calcination is a hexagonal α-Ga2O3 crystal, in which the diffraction peaks at 35.90° and 63.33° on the XRD spectrum correspond to the (110) and (214) crystal planes of α-Ga2O3, respectively.
[0031] Figure 2 b and Figure 2 c are FE-SEM photos of GaOOH nanocrystals and α-Ga2O3, respectively. It can be clearly observed from the figure that the particles are microspherical, with relatively uniform morphology and size, compact composition, smooth surface, and a diameter distribution range of about 500nm. The calcined α-Ga2O3 particles have good morphology and size inheritance.
[0032] Figure 3 a, b are the FT-IR spectrum and fluorescence emission spectrum of GaOOH / α-Ga2O3 microspheres, respectively. Figure 3 a It can be seen that at the wave number of 3300~3400cm -1 The absorption band at 1650cm is due to the stretching vibration of the HOH bond in the H2O molecule. -1 There is a broad absorption band near 2340 cm, which may be the overlap of the OH bond bending vibration absorption band in the adsorbed H2O molecules and the hydroxyl vibration absorption band in the sample. -1 The faint peaks on the left and right and 1360cm -1 The absorption peaks on the left and right can be attributed to the C=O symmetrical structure of CO2 adsorbed from the air by the sample, and the absorption peaks at 954 cm -1 The absorption peaks on the left and right are caused by the inversion deformation of Ga-OH, 643cm -1 and 510cm -1 The absorption peaks on the left and right are the bending vibration peaks of the Ga-O structure in α-Ga2O3.
[0033] from Figure 3 b, a broad peak from 320nm to about 600nm can be observed, among which there are four obvious fluorescence emission peaks, corresponding to the wavelengths of ultraviolet light around 360nm, purple light at 406nm, blue light at 472nm and green light at around 510nm, and the peak intensity of blue light is relatively strong. The ultraviolet emission originates from the recombination of free electrons and self-trapped holes, and the photoluminescence phenomenon of α-Ga2O3 is related to the Ga vacancy, O vacancy and Ga-O vacancy pair (V O -V Ga ). The purple and blue bands may originate from the V O The captured excited electrons and V Ga The green band may originate from the relaxation of self-trapped excitons or vacancy / defect bound excitons. Compared with the blue light 500nm emitted by commercial α-Ga2O3 crystals, the blue light emitted by the nano-α-Ga2O3 prepared by us has a significant blue shift. This phenomenon may be caused by the quantum size effect of nanomaterials. As the particle size decreases, the energy gap width becomes larger, resulting in the emission spectrum moving toward the shorter wavelength direction.
[0034] In order to verify the influence of the composite template on the material in this case, the following comparative experiment is provided in this case.
[0035] Comparative Example 1:
[0036] The conditions were the same as those in Example 1, except that only DL-aspartic acid was added as a template, and the precursor material was prepared by a simple atmospheric pressure reflux low-temperature hydrothermal method.
[0037] like Figure 4 As shown in the figure, compared with the GaOOH nanocrystals prepared by composite soft template induction (Example 1), the morphology is more irregular, the sphere size is less uniform, the loose microspheres are adhered to each other, the surface is relatively rough, and a small number of microspheres have not yet formed. The size distribution range of the microspheres in the figure is 150nm to 300nm, which is smaller than the size of the microspheres in Example 1. From the TEM photo of GaOOH microspheres ( Figure 4 c, d) It can be seen that the microspheres are loosely composed, and the orderly accumulation of nanoparticles on the rough surface also indirectly indicates that the microspheres are formed by the self-assembly of small nanoparticles. When PEG-4000 is missing as a stabilizer to control particle growth, Ga 3+ The DL-aspartic acid molecules are dispersed in the water medium only by electrostatic action, so that after the reaction generates small particles, the small particles are prone to grow or irregular aggregation between the small particles occurs, thereby generating an irregular microsphere structure.
[0038] Comparative Example 2:
[0039] The conditions were the same as those in Example 1, except that only PEG-4000 was added as a template, and the precursor material was prepared by a simple atmospheric pressure reflux low-temperature hydrothermal method.
[0040] like Figure 5 As shown in the figure, it can be seen that the GaOOH crystal is in a rod-shaped, quadrangular prism structure, the length and width of the rod are distributed in the range of 0.7μm to 1.3μm and 150nm to 250nm, respectively, the morphology and size distribution are relatively uniform, the surface is relatively rough, and the arrangement of small particles is relatively irregular. Compared with the GaOOH in Example 1, the system does not add the organic small molecule DL-aspartic acid, and the electrostatic attraction of the groups contained in it cannot be used to bind Ga 3+ Pulling to the surface of PEG-4000 cannot promote the orderly accumulation of GaOOH nanoparticles on the surfactant. At the same time, due to the lack of protection of DL-aspartic acid on the generated GaOOH particles, it is difficult to obtain solid particles that aggregate like balls, thus turning into a rod-like morphology.
[0041] Comparative Example 3:
[0042] The conditions were the same as those in Example 1, except that no template was added, and the precursor material was prepared by a simple atmospheric pressure reflux low-temperature hydrothermal method.
[0043] like Figure 6 The following are FE-SEM and TEM images of GaOOH prepared by a simple atmospheric reflux hydrothermal method. Figure 4 From a and b, we can see that GaOOH crystals are regular rod-shaped, the rod-shaped structure is relatively loose, the length distribution range of the rod is 0.7μm to 1.1μm, the morphology and size are relatively uniform, and the transmission electron microscope photos Figure 4 c and d match.
[0044] Application examples:
[0045] Weigh 0.0500g of calcined gallium oxide powder and place it in a 200mL quartz reaction bottle, then add 50.00mL of 10mg / L methyl violet aqueous solution and transfer it to the inner chamber of the photoreactor, stir for 1h in a dark place to allow the system to reach adsorption-desorption equilibrium, then irradiate with a UV lamp with a wavelength of 254nm and a power of 150W and a xenon lamp with a wavelength of 420nm and a power of 300W under a constant temperature water bath at 25°C while stirring (the quartz reaction bottle is 10cm away from the light source), the irradiation time is 100min, and sampling is performed at intervals of 20min, taking 5.0mL of solution each time, centrifugally filtering, and using a UV-visible absorption spectrometer to measure the absorption spectrum of the supernatant. The absorbance of the methyl violet solution is converted into decolorization rate according to the following formula:
[0046] X=(A0-A t) / A0×100%
[0047] In the formula, A0 is the initial absorbance of the solution, A t —The absorbance of the solution at time t.
[0048] from Figure 7 b curve analysis shows that under the combined action of the catalyst and methyl violet, the absorbance of the catalytic reaction system decreases linearly with time. The structure of methyl violet contains N-methyl, which is easily attacked by OH free radicals and undergoes demethylation degradation reaction, which is manifested in the maximum absorption wavelength (λ max ) blue shift. With the extension of photocatalytic degradation time, methyl violet can be mineralized into NO2, CO2, H2O and other inorganic ions. The reason may be: under ultraviolet light irradiation, the electrons in the valence band are excited to jump to the conduction band, so that holes are generated in the valence band and photogenerated electrons are formed in the conduction band. Due to the band gap between the valence band and the conduction band, the holes and photogenerated electrons have a long enough lifetime before recombination and migrate to the surface of the photocatalyst α-Ga2O3. Photogenerated holes have strong oxidizing properties and can capture electrons in water adsorbed on the surface of α-Ga2O3 particles to generate HO·, while photogenerated electrons can migrate to the surface of α-Ga2O3 particles and be oxidized. The above reactions can produce a variety of highly reactive reaction intermediates and free radicals, such as HO·, ·O 2- 、O2 - and H2O2, etc., prompting the system under catalytic light to undergo a series of meaningful oxidation and reduction reactions, and the methyl violet molecules are degraded until they are completely converted into small molecules such as CO2, NO2 and H2O.
[0049] In summary, this case uses gallium nitrate as gallium source and urea as homogeneous precipitant, and successfully synthesizes GaOOH microsphere structure with relatively uniform morphology and size in PEG4000-DL-aspartic acid composite soft template system through simple atmospheric pressure reflux method, and the particle size is about 500nm. Experiments show that the morphology of the precursor prepared by DL-aspartic acid system is relatively regular, the particle size is relatively uniform and the distribution range is 150nm~300nm, which is similar to microspheres; the precursor prepared by PEG4000 system is a rod-shaped structure with a quadrangular prism cross-section, and its morphology and size distribution are relatively uniform, with a length range of 0.7μm~1.3μm and a width range of 150nm~250nm; the GaOOH obtained by the system without any additives is a rod-shaped micro-nano material with a length distribution range of 0.7μm~1.1μm. The results show that the addition and dosage of DL-aspartic acid have a great influence on the morphology and size of GaOOH microspheres, while the addition of PEG4000 is conducive to the formation of microspheres with uniform morphology and size, indicating that the composite soft template formed by PEG4000-DL-aspartic acid plays a vital role in the controlled synthesis of GaOOH and α-Ga2O3 microsphere nanostructures, and its template function can be fully exerted under appropriate ratio conditions. After calcination of the microspherical GaOOH nanostructure, α-Ga2O3 microspheres with well-maintained morphology can be obtained, and the decolorization rate of methyl violet aqueous solution within 100 minutes is 99.85%, indicating that the experimentally prepared α-Ga2O3 microspheres have good photocatalytic properties.
[0050] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing micro-nanostructured gallium oxide, characterized in that: The steps include: S1: Add DL-aspartic acid and deionized water to a reaction bottle, dissolve by ultrasonication, then add PEG solution, gallium nitrate solution and urea to the solution in sequence, stir and mix evenly to obtain a colorless, clear and transparent solution; the mass ratio of DL-aspartic acid to PEG is 0.04:0.4-0.04:6; S2: The colorless, clear and transparent solution is then heated from room temperature to boiling until a white precipitate appears in the system and the turbidity no longer increases, and the pH value of the solution is adjusted to 6, and the system is in a sol state; S3: Keep the system in a boiling state and continue stirring for 3 h, then stop heating and cool naturally to room temperature. After natural sedimentation for about 10 h, separate the precipitate and wash it with distilled water and anhydrous ethanol three times each, and finally vacuum dry it at 60°C for 12 h to obtain the precursor material; S4: The precursor material is loaded into a corundum crucible and placed in a muffle furnace, and calcined at 450°C for 3 h to obtain α-Ga2O3 nanomaterials.
2. The method for preparing micro-nanostructured gallium oxide according to claim 1, characterized in that: The molecular weight of the PEG is 4000, and the concentration of the prepared PEG solution is 0.1 mol / L.
3. The method for preparing micro-nanostructured gallium oxide according to claim 1, characterized in that: The concentration of the gallium nitrate solution is 0.2 mol / L, and the volume mass ratio of the gallium nitrate solution to DL-aspartic acid is 0.5 ml:0.02 g~0.5 ml:0.05 g.